PERAN STORE IMAGE DAN CONTENT MARKETING TERHADAP REPURCHASE INTENTION YANG DI MEDIASI CUSTOMER SATISFACTION (Studi pada Pelanggan NTB Mall di Kota Mataram): PERAN STORE IMAGE DAN CONTENT MARKETING TERHADAP REPURCHASE INTENTION YANG DI MEDIASI CUSTOMER SATISFACTION (Studi pada Pelanggan NTB Mall di Kota Mataram) - Yuni Kartika Wulandari; Vania, Amelindha (JURNAL EKBIS, 2023)
This study aims to determine the effect of Store Image and Content Marketing on Repurchase Intention with Customer Satisfaction as a moderating variable for NTB Mall customers in Mataram City. The research method used is a descriptive quantitative approach, namely an explanation of the number measurement system using purposive sampling technique. The number of samples determined in this study were 90 respondents who had made purchases at the NTB Mall. The results and conclusions found are that Store image and content marketing have a positive and significant influence on Customer Satisfaction, and Store image and content marketing also have a positive and significant influence on Repurchase Intention for NTB Mall consumers. However, the role of Customer Satisfaction is not able to mediate the relationship between Store image and content marketing on Repurchase Intention for NTB Mall consumers.